Computer Design Starts Over. - DeBenedictis, Erik P. (Computer (00189162), 2017)
To maintain Moore’s law, the semiconductor industry decided a decade ago that a new transistor was imperative. That silver bullet has yet to materialize, but computer design innovations are now maintaining or even exceeding expected scaling progress. This theme issue gives a cross-sectional view of these new scaling drivers.